Prevalência de dor crônica nas pessoas idosas do município de Coxilha/RS - Moraes, Joana Stela Rovani de (2025)
The existence of pain has always intrigued humanity. With the work of science, knowledge has supplanted the complaint of pain as a single symptom, and determined that pain is the disease itself, especially when accompanied by the term chronic. Although normal aging should not be directly linked to a continuous state of pain, it is known that the population over 60 years of age has more pain. Thus, this study sought to answer what is the prevalence of chronic pain in the elderly in the city of Coxilha/RS and, in the same way, describe the prioritized management, with the aim of future interventions in socio-educational, nonpharmacological projects, focusing on improving the quality of life of patients. The main result of this study was the prevalence found of chronic pain, which was recorded at 68.4%. Regarding the outcome chronic pain, this prevailed in the group of elderly people who used between 1 and 4 medications for pain, in female participants and in those over 80 years of age. Rest and massage were the most commonly used non-pharmacological measures, while duloxetine hydrochloride, paracetamol, dipyrone and amitriptyline hydrochloride were the most commonly used drugs by those with chronic pain. Although these are the most commonly prescribed drugs today, there are few studies involving people in their sixties and older, who are generally excluded from major clinical trials precisely because of their side effects. In conclusion, this study shows a high prevalence of chronic pain in a population that is growing considerably, with longer life expectancies, and that currently does not have many pharmacological options, nor does it have non-pharmacological public policies available that appear to be concerned with this long-term demand.